Almitrine bismesylate and oxygen therapy in hypoxic cor pulmonale. Issue 1 (January 1990) - Evans, T W; Tweney, J; Waterhouse, J C; Nichol, J; Suggett, A J; Howard, P
Abstract : The effect of oral treatment with the thiazine derivative almitrine bismesylate was studied in 28 patients with chronic obstructive pulmonary disease and arterial hypoxaemia receiving long term domiciliary oxygen therapy in a placebo controlled, double blind crossover trial. The initial treatment was given for three months and the second for two months. Because almitrine had an unexpectedly prolonged washout effect crossover analysis could not be performed; data from the placebo treatment administered in the second arm of the trial were used to calculate the half life of almitrine. Nine patients were withdrawn from the study (5 almitrine, 4 placebo). Patients' tolerance of the drug was good. The estimated plasma half life of almitrine was 20.5 days, considerably longer than previously reported. Almitrine caused a significant improvement in arterial oxygen tension (PaO2) with a mean maximum increase of 0.7 kPa at a plasma concentration of 500 ng/ml. Higher plasma concentrations were not associated with any further increase in PaO2. There was no significant effect on arterial carbon dioxide tension (PaCO2). In a second, acute study at the end of each arm of the chronic trial nine patients were subjected to increasing oxygen delivery rates (2, 4, and 6 l/min) for 90 minutes or until blood gas concentrations plateaued. Almitrine increased PaO2 in a dose dependent fashion at all delivery rates, but the effect diminished as PaO2 approached normoxic levels. There was no significant effect on PaCO2. Almitrine treatment results in a significant improvement in PaO2 over that achieved by oxygen alone, an effect that diminishes at high flow rates. Whether this is of clinical benefit is not known. In view of the prolonged half life revised dosage schedules are required.